Macroeconomic factors driving exchange rate volatility and economic sustainability: Case study of Pakistan - Saghir Pervaiz Ghauri; Rizwan Raheem Ahmed; Dalia Streimikiene; Hina Qadir; Anum Hayat (Amfiteatru Economic Journal, 2024)
Volatility increases the risk of exchange rate, and the risk of exchange rate refers to losing money due to fluctuations in the exchange rate. Thus, it significantly impacts the country's economic development stability or sustainability, as making investment and trade decisions under volatile exchange rates is complicated. The macroeconomic stability of the Sustainable Development Goals (SDGs) of the United Nations can only be achieved partially with the fluctuation of the exchange rate in a country. Therefore, to stabilise exchange rate fluctuations, Pakistan's policy makers are making determinations about the US dollar specifically, which is one of the main reasons why this research study aims to identify the macroeconomic factors that determine the volatility of exchange rates in Pakistan; therefore, for this research study, annual data is used. This study uses an Autoregressive distribution lag (ARDL) model, which assesses cointegration between variables to see their short- and long-term relationship. As a result, there is cointegration, according to the results of the ARDL bound test. Furthermore, in short- and long-period relationships, debt, interest rates, and political stability are revealed to have statistically significant consequences on currency rate volatility. Finally, the Granger causality test analyses that terms of trade, debt, political stability, and inflation cause fluctuations in the exchange rate. On the contrary, the volatility of the exchange rate affects the country's current account. As a result, it is stated that, except for current account balance and interest rate from Granger causality, all the macroeconomic factors selected in this study are drivers of exchange rate volatility. However, the vital common determinants from the ARDL and Granger test are debt and political stability, which influence exchange rate fluctuation and hamper the country's economic sustainability. This study implies that the government should also reduce its debt financing by reducing its non-productive expenditure and ensuring political stability, essential for stabilising the exchange rate. This macroeconomic stability can increase the impact of the market rate to influence foreign direct investment, leading to appreciation of the currency and sustainable economic growth of the country.
Keywords: F31; F40; 330; volatility of exchange rate; macroeconomic determinants; economic sustainability; Granger causality test; ARDL bound test